2022
DOI: 10.3390/foods11182804
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Untargeted Analysis of Volatile Compounds in Four Red Grape Varieties (Vitis vinifera L. cv) at Different Maturity Stages near Harvest

Abstract: Grape volatile compounds directly determine the aroma quality of wines. Although the aroma profile of grapes evolved greatly at different maturity stages, there were less considerations for aroma status when determining grape harvest time. In the present study, several maturation indicators, namely, sugars/acids ratio, free volatile compounds, bound volatile compounds and IBMP (3-isobutyl-2-methoxypyrazine) content were monitored in four red wine grape varieties (Vitis vinifera L. cv Cabernet Sauvignon, Cabern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The flavour composition of a wine generally includes its aroma, taste, and mouth-feel [ 1 ], which are arguably the most important contributors that influence wine quality. In general, wine aroma can be divided into the varietal aroma (the fruit type of the aroma), fermentation aroma (the second type of aroma), and aging aroma (the third type of aroma), according to different sources [ 2 ]. The taste is primarily defined by non-volatile compounds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The flavour composition of a wine generally includes its aroma, taste, and mouth-feel [ 1 ], which are arguably the most important contributors that influence wine quality. In general, wine aroma can be divided into the varietal aroma (the fruit type of the aroma), fermentation aroma (the second type of aroma), and aging aroma (the third type of aroma), according to different sources [ 2 ]. The taste is primarily defined by non-volatile compounds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… Free-form alcohols, esters, and terpene concentrations increased during ripening and decreased in overripe stages. Gu et al, 2022 Climatic Factor 45–50; airflow rates of 750 fpm Raisin Thompson Seedless Flame Seedless Produced better color and sweet taste as compared to sun-dried raisins Gee, 1980 40 °C + lyophilization 70, 65, and 60 °C + lyophilization, 70 °C + lyophilization Raisin Bezsemenné Perlette Vrboska Jakubské, Beauty seedless 40 °C + lyophilized had the best sensory quality in terms of smoothness, gloss, color, odor, chewability, juiciness, flavor, and overall impression as compared to the higher temperature Langová et al, 2020 30 °C 40 °C 50 °C Raisin Zicui Raisins dried at 50 °C had the highest levels of glucose, fructose, malic acid, shikimic acid, and succinic acid. Drying at 40 °C preferred the accumulation of various phenols while at 30 °C favored the accumulation of anthocyanins, flavonoids, and flavanols.…”
Section: Factor Affecting Raisin Aromamentioning
confidence: 99%
“…Grapes that are harvested at different stages of ripeness will have different levels and types of volatile components. Therefore, to identify the optimal harvesting time, Gu et al (2022) conducted a study on four grape varieties (Cabernet Sauvignon, Cabernet Gernischet, Cabernet Franc, and Merlot) harvested at seven different times from 3 September to 15 October, with 7-day intervals. They concluded that the peak sugars/acids ratio was achieved on day 21 for Merlot and on day 28 for the other three varieties.…”
Section: Factor Affecting Raisin Aromamentioning
confidence: 99%
“…The volatile profile we obtained in this study can also be compared with the profile obtained in bunch grapes (V. vinifera). Gu et al [17] monitored four red wine grape varieties (V. vinifera cvs. Cabernet Sauvignon, Cabernet Gernischet, Cabernet Franc, and Merlot) near harvest time for their aroma volatile composition and found a very similar pattern of volatile composition during berry ripening.…”
Section: Role Of Berry Maturity On Volatile Compositionmentioning
confidence: 99%
“…The composition and abundance of aroma volatiles are linked with the fruit maturity and level of ripeness. Studies have shown differences in volatile composition in the different ripening stages of bunch grapes [17], raspberries [18], bananas [19], lulos [20], figs [21], and muskmelons [22]. However, no research has been conducted to understand the effect of berry ripeness on the aroma volatile composition of muscadines.…”
Section: Introductionmentioning
confidence: 99%